2022
DOI: 10.15252/embj.2021109992
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy–mediated plasma membrane removal promotes the formation of epithelial syncytia

Abstract: Epithelial wound healing in Drosophila involves the formation of multinucleate cells surrounding the wound. We show that autophagy, a cellular degradation process often deployed in stress responses, is required for the formation of a multinucleated syncytium during wound healing, and that autophagosomes that appear near the wound edge acquire plasma membrane markers. In addition, uncontrolled autophagy in the unwounded epidermis leads to the degradation of endo‐membranes and the lateral plasma membrane, while … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 85 publications
(107 reference statements)
2
19
0
Order By: Relevance
“…Autophagy is a common process in development, differentiation, and tissue remodeling and is activated during wound healing in Drosophila and other species [ 71 ]. Studies in Drosophila showed that autophagy can also have cytoprotective functions [ 72 ] and induces formation of multinucleated giant cells [ 73 ]. Drosophila larvae have elevated levels of autophagy in the epidermis, both during development and epidermal wound healing [ 73 ].…”
Section: Molecular Promoters and Repressors Of Aging And Growth—a Les...mentioning
confidence: 99%
See 2 more Smart Citations
“…Autophagy is a common process in development, differentiation, and tissue remodeling and is activated during wound healing in Drosophila and other species [ 71 ]. Studies in Drosophila showed that autophagy can also have cytoprotective functions [ 72 ] and induces formation of multinucleated giant cells [ 73 ]. Drosophila larvae have elevated levels of autophagy in the epidermis, both during development and epidermal wound healing [ 73 ].…”
Section: Molecular Promoters and Repressors Of Aging And Growth—a Les...mentioning
confidence: 99%
“…Studies in Drosophila showed that autophagy can also have cytoprotective functions [ 72 ] and induces formation of multinucleated giant cells [ 73 ]. Drosophila larvae have elevated levels of autophagy in the epidermis, both during development and epidermal wound healing [ 73 ]. Autophagy induces cell membrane breakdown, facilitating cell fusion and the formation of giant syncytial cells [ 73 ].…”
Section: Molecular Promoters and Repressors Of Aging And Growth—a Les...mentioning
confidence: 99%
See 1 more Smart Citation
“…Kakanj et al set out to investigate whether autophagy could be involved in wound healing using a refined and powerful video microscopy set up with anaesthetized larvae triggered by single‐cell laser‐induced wounding (Kakanj et al , 2022). This allows highly stereotypic manipulation, and detailed observational and genetic analyses of wound healing dynamics that is completed within 2–3 h. Using fluorescently tagged Atg8a that label the autophagic membranes, they verified that autophagy markers were increased in cells surrounding the wound and peaked at about 120 min after injury, when wound closure is nearly complete.…”
Section: Figure Autophagy Promotes Syncytium Formation During Wound H...mentioning
confidence: 99%
“…The lysosomal degradation pathway of autophagy depends on a set of evolutionarily conserved autophagy-related molecules (ATGs) bestowed with the power to direct membrane trafficking and biology. In this issue of EMBO Journal, Kakanj P et al reveal a surprising role for the autophagy machinery in cell fusion (Kakanj et al, 2022). Autophagy is physiologically required for cell syncytium formation through dismantling the lateral plasma membrane during wound healing, and unchecked autophagy can drive cell fusion in epithelial tissues without compromising epithelial integrity.…”
mentioning
confidence: 99%